Fairy-tale revivals in the long nineteenth century.
1 online resource
Keywords: This collection opens with marginalized responses to the highly politicized Cinderella traditions in the Anglophone world. In the United States, Cinderella was incorporated into the gendered narrative of the American Dream and narratives of empire in the colonial world, particularly in the mid-1800s. Marginalized writers have responded to these nationalistic colonial traditions in two distinctive ways: clever Cinderellas who negotiate a broken system or passive Cinderellas who die as anti-heroes in disenchanting fairy tales. This dual tradition of marginalized Cinderellas is also apparent across the Anglophone world. Potential texts include the out-of-print works of Sinad de Valera, excerpts from the novels of Hannah Crafts, Jessie Fauset, and Julia Kavanagh, along with dramas by Ann Devlin, and collected oral tales.